The Relationship Between Self-Confidence and Entrepreneurial Motivation of Graduates of Sewing Training Participants at UPTD BLK Payakumbuh - Safitiri, Tiara; 'Aini, Wirdatul (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
The background of this research by the low entrepreneurial motivation of graduates participating in sewing training at UPTD BLK Payakumbuh, this was due to the self-confidence of the graduate participants. This research aims to reveal a picture of self-confidence, entrepreneurial motivation, and the relationship between self-confidence and entrepreneurial motivation of graduates of sewing training participants at UPTD BLK Payakumbuh. This research is a correlational type of quantitative research. The population in this study was 32 graduates participating in sewing training. The sampling technique uses proportional random sampling. The sample was taken as 21% of the population, namely 25 graduates participating in sewing training. The data collection technique uses a questionnaire. The data analysis technique uses presentation formulas and the Sprearman Rho correlation formula.  The results of this study show: 1) the self-confidence of sewing training graduates is relatively low; 2) the entrepreneurial motivation of sewing training participants is low; 3) there is a significant relationship between self-confidence and entrepreneurial motivation of graduates of sewing training participants at UPTD BLK Payakumbuh.Suggestions in this research are expected for graduate training participants. It is hoped that graduate participants will always try to raise their self-confidence and enthusiasm to be motivated in starting a business so that the skills and knowledge gained during the sewing training can be developed.Keywords: Self-confidence, Entrepreneurial Motivation